Promosi Produk Kulit Melalui Event Astiga Edu Vacation - Arif, Muhammad Salman; Maryani, Anne; Chaerowati , Dede Lilis (Communicatus: Jurnal Ilmu komunikasi, 2026)
The fashion business in Indonesia continues to grow, including leather-based fashion that has become a distinctive characteristic of Garut City. One of the local fashion businesses is Astiga Leather, which faces intense competition and therefore needs a unique promotional strategy. This study aims to examine the promotion of leather products through the Astiga edu vacation event. The research uses a qualitative method with a case study approach and a constructivist paradigm, The research subjects were determined using purposive sampling. Data were collected through observation, interviews, documentation, and literature study. The results show that Astiga Leather’s promotional activities include active engagement on social media, participation in fashion shows, offering discounts, and organizing the Astiga edu vacation event. The event is promoted through direct offers, collaborations with travel agents and educational businesses, exhibitions, and brochure distribution. The main promotional medium used is Instagram, supported by Facebook, TikTok, and the company’s website. The challenges encountered include promoting the event effectively, aligning educational materials with consumer characteristics, and technical barriers such as language differences and venue constraints. The Astiga edu vacation program aims to provide education about leather craftsmanship, turn consumers into product promoters, deliver a unique promotional experience, and increase the sales of Astiga Leather products. Keywords : Marketing Communication; Media Promotion; Astiga Edu Vacation; Leather Jacket.